Dimensons of Deviations from the Principles of the Qira’at in Nigeria - Musa, Ismail a. (The Journal of Rotterdam Islamic and Social Sciences, 2014)
This article looks at various dimensions of the violations of the principles of Qirā’āt in Nigeria and recommends intervention. Samples of Qur’anic recitations by a broad spectrum of Muslims in six states were recorded and subsequently analysed, focussing mainly on the extent of compliance with the ethos of the Warsh and Hafṣ methods. The investigation revealed the preponderance of the aberrant forms of Qur’anic recitation over the ideal typologies. The anomalous types of recitations were prevalent among the ordinary Muslims while the ideal typologies are found mainly among scholars. Apart from commingling the principles of the Riwayātu Hafṣ and Riwayatu Warsh, the rules violated cover those governing the Isticādhah and Basmalah, al-Imālah (vowel Harmony), an-Naql, (transferring), al-Ibdāl, (substitution), at-Tashīl (easing), al-Ishmām (lip rounding) and ar-Rawm (slight vocalisation). Similarly, principles shared by both Tajwīd and cIlmul-Qirā’āt were equally violated. Such rules include al-Idghām (assimilation), al-Izhār (manifestation), al-Ikhfā’ (concealment), al-Madd (prolongation) and al-Waqf (pausing). The study proposes a number of interventions, including strategies of increasing access to the study of Qirā’āt through authorship of books in English and Nigerian as well as the teaching of the Qirā’āt in the context of Tajwīd or as an independent subject.